Assessment by competences in Vocational Training: A systematic review of the Spanish scientific production - Nieto Ortiz, Jorge; Roa González, Julián; Lucas Barcia, Elisa (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Legislative reforms in vocational training have forced a paradigm shift and have favoured a competency-based approach with direct consequences for evaluation. In this systematic review work, the publications related to the evaluation in VET with a classification higher than D in CIRC during the period 2011-2021 have been analysed. The main results indicate a low production with a peak period in 2017-2018, with a tendency to punctual publication in pairs, but with a moderate impact. The new legislative reality and the new educational approaches invite a need to promote research in this field.